Socio-anthropological analysis of bariatric surgery patients: a preliminary study - Julia Navas López (Social Medicine Publication Group, 2024)
Using socio-anthropological analysis, this paper presents preliminary results of an inter-disciplinary investigation entitled "A nutritional and anthropological study of patients with type III and IV obesity undergoing bariatric surgery." The medical ethnographic approach employed in this study has two goals: to study patients' cultural context before and after surgical treatment and to analyze perceptions, representations, social inte-gration, stigmatization, and social control before and after surgery. The results show potential discrimination against these patients based on their group identification and a permissive environment; these ideas are manifested in the concepts of the "obesogenic society" and the "obese victim." On the other hand, the process of medicalization provides a mechanism capable of both social inclusion and exclusion. The results of this preliminary analysis are informing ongoing work between patients and professionals in this nutritional study.